Implementing Sharia Economic Principles in Pesantren-Based Digital Business Activities - Dina Sonia; Achmad Farid (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
The rapid development of digital technology has encouraged Islamic educational institutions, including Pesantren Mamba’ul Falah, to participate in digital entrepreneurship while maintaining Islamic ethical values and institutional traditions. This study aims to analyze the implementation of sharia economic principles in pesantren-based digital business activities and examine how the pesantren manages digital entrepreneurship within a supervised educational environment. This research employed a qualitative descriptive approach using a case study design. Data were collected through interviews, observations, and documentation involving pesantren leaders, administrators, and students engaged in digital business activities. The findings reveal that the implementation of sharia economic principles is reflected in honesty in digital marketing communication, trustworthiness in transaction management, fairness in pricing and customer service, and transparency in online transactions. The pesantren also attempts to avoid prohibited elements such as riba, gharar, and unethical promotional practices through institutional supervision and controlled digital access. In addition, restrictions on smartphone usage demonstrate the pesantren’s effort to balance technological adaptation with moral discipline and educational values. This study concludes that pesantren-based digital entrepreneurship represents a unique model of Islamic economic adaptation that integrates digital business practices with sharia compliance, moral education, and institutional responsibility.